2019
DOI: 10.1158/2326-6066.cir-18-0386
|View full text |Cite
|
Sign up to set email alerts
|

Anti–CTLA-4 Activates Intratumoral NK Cells and Combined with IL15/IL15Rα Complexes Enhances Tumor Control

Abstract: Antibodies targeting CTLA-4 induce durable responses in some patients with melanoma and are being tested in a variety of human cancers. However, these therapies are ineffective for a majority of patients across tumor types. Further understanding the immune alterations induced by these therapies may enable the development of novel strategies to enhance tumor control and biomarkers to identify patients most likely to respond. In several murine models, including colon26, MC38, CT26, and B16 tumors cotreated with … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
62
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(69 citation statements)
references
References 23 publications
6
62
0
1
Order By: Relevance
“…2F). These data support recent findings that NK cells within mouse tumors can be functionally modulated by ICI treatment Sanseviero et al, 2019).…”
Section: Cogaps Analysis Identifies a Subset Of Activated Nk Cells Insupporting
confidence: 92%
See 1 more Smart Citation
“…2F). These data support recent findings that NK cells within mouse tumors can be functionally modulated by ICI treatment Sanseviero et al, 2019).…”
Section: Cogaps Analysis Identifies a Subset Of Activated Nk Cells Insupporting
confidence: 92%
“…In B16 melanoma models, NK cells and CD8+ T cells synergistically clear tumors in response to anti-CTLA-4 and IL-2 treatment (Kohlhapp et al, 2015). Furthermore, anti-CTLA-4 has been shown to increase transcriptional markers of NK cell cytotoxic activity in CT26 colon carcinoma tumors (Sanseviero et al, 2019). In aggregate, those studies did not provide mechanistic bases for the identified associations.…”
Section: Discussionmentioning
confidence: 98%
“…They found that anti-CTLA-4 binding to FcRs has been linked to depletion of intratumoral Tregs, and further coincided with activation and degranulation of intratumoral NK cells. Combination therapy with anti-CTLA-4 plus IL15/IL15Rα complexes enhanced tumour control compared with either monotherapy [ 169 ]. Fc-region–modified anti-CTLA-4 mAb with high antibody-dependent cell-mediated cytotoxicity (ADCC) and cellular phagocytosis (ADCP) activity selectively depleted CTLA-4 + Foxp3 + Tregs and consequently expanded tumour antigen-specific CD8 + T cells.…”
Section: Tumour Immunotherapy Strategies Targeting Tregsmentioning
confidence: 99%
“…Moreover, anti-CTLA-4 combined with IL-15/IL-15Rα enhances the NK cell tumor infiltration, improving the tumor growth control in xenograft murine models of solid tumors. Melanoma patients treated with anti-CTLA-4 (ipilimumab) had higher intratumoral CD56 expression(171). Consistently, several phase I and II clinical trials are ongoing to test the efficacy of different anti-PD1, anti PD-L1, and anti-CTLA-4 mAbs, alone or in combination with other Abs, in multiple forms of advanced and metastatic solid tumors (…”
mentioning
confidence: 92%